The influence of mesh size and shape on the size selection of European hake (Merluccius merluccius) in demersal trawl codends: An investigation based on fish morphology and simulation of mesh geometry - Tokaç, Adnan; Herrmann, Bent; Gökçe, Gökhan; Ahm Krag, Ludvig; Sadegh Nezhad, Davud (Scientia Marina, 2018)
European hake (Merluccius merluccius) is an important commercial species for several European bottom trawl fisheries. Therefore, understanding the influence of codend mesh size and shape on the size selection of European hake is critical for defining technical measures for fisheries targeting this species. Based on morphology data collected on European hake, the influence of mesh size and shape on bottom trawl codend size selectivity was investigated by simulation using the FISHSELECT methodology successfully applied previously for other species. The predicted size selection for European hake was found to agree well with previous experimental results for a wide range of mesh sizes if it was assumed that the codend meshes had a relatively small opening angle, between 20° and 40°, during trawling. This study enables detailed prediction of size selectivity for European hake and offers a potential explanation for previous experimental size selectivity results.